Executive Director’s Message - Dow, Heather (Operating Room Nurses Association of Canada Journal, 2017)
At the May 2017 ORNAC National Conference we were pleased to release the 13th Edition of the ORNAC Standards, Guidelines and Position Statements for Registered Nurses.